Improving Qur’anic Literacy through the Tafahhum Method: A Qualitative Case Study - Herlin Misliani (Newinera Publisher, 2026)
This study examines the use of the tafahhum method in improving Quranic literacy among students at the Institut Ilmu Al Quran Jakarta. It begins from the concern that Quranic learning often emphasizes fluent recitation and memorization more than meaningful understanding. Using a qualitative case study design, the research involved 30 undergraduate students from the 2022 cohort and 3 lecturers of tahsin and tahfiz. Data were collected through classroom observations, semi structured interviews, documentation, and student response sheets used as supporting descriptive material. The findings show that students’ Quranic literacy was generally strong in recitation, but still uneven in tajwid accuracy and comprehension of meaning. Tafahhum was practiced in tahsin, tahfiz, and murojaah sessions through guided explanation, reflective engagement, and contextual connection between verses and everyday life. However, not all students were able to engage the process equally well. Some still struggled to explain the meanings of memorized verses, connect verses thematically, and relate Quranic messages to lived experience. These difficulties were influenced by differences in Arabic proficiency, educational background, interpretive readiness, and confidence in active participation. The study concludes that tafahhum plays an important role in bridging recitation and comprehension. Its successful implementation, however, depends on sustained pedagogical guidance, contextual learning, language support, and collaborative classroom practices that help students engage the Quran as both a recited and meaningful text.